Agriculture Systems - Andren, O.; Katterer, T (Elsevier, 2008)
An agricultural ecosystem is an ecosystem managed with a purpose, usually to produce crops or animal products. Agricultural ecosystems are designed by humans, and are based on a long chain of experience and experiments. The emphasis in, for example, Western Europe has changed from maximum productivity only to also include environmental considerations, such as reduction of nutrient losses to groundwater and maintaining an open landscape with high biodiversity, etc. In less-productive regions such as sub-Saharan Africa, environmental considerations still have low priority. Agricultural ecosystems comprise almost 40% (5 Gha) of the total land area of the Earth. About 11% of the total land area is arable land (cultivated with crops), and approximately 27% of the total land area is under permanent pasture, grazed by cattle, goats, sheep, camels, etc. Plant biodiversity is extremely low – if weed control is successful there may be only one species present. In spite of this, belowground biodiversity can be high, although often lower than in natural ecosystems. Ecological research performed in agricultural systems has advantages compared with research in most natural ecosystems, since agricultural fields are ‘homogenized’, that is, trees, larger stones, etc. are removed and regular soil cultivation to some extent evens out differences in topsoil properties over time.